2006
DOI: 10.1002/jnr.20781
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia inhibitory factor is produced by myelin‐reactive T cells from multiple sclerosis patients and protects against tumor necrosis factor‐α‐induced oligodendrocyte apoptosis

Abstract: In multiple sclerosis (MS), damage to oligodendrocytes is believed to be caused by an aberrant immune response initiated by autoreactive T cells. Increasing evidence indicates that these T cells are not exclusively detrimental but might also exert protective effects. We report for the first time that myelin-reactive T-cell clones from eight MS patients (6/19) and five healthy controls (4/11) produce leukemia inhibitory factor (LIF), a member of the neuropoietic family of neurotrophins. In addition, T-cell clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 59 publications
1
46
1
1
Order By: Relevance
“…In a genetic study, no association was found between these DNA polymorphisms and the prevalence of MS [58].…”
Section: Leukaemia Inhibitory Factor (Lif)mentioning
confidence: 80%
See 1 more Smart Citation
“…In a genetic study, no association was found between these DNA polymorphisms and the prevalence of MS [58].…”
Section: Leukaemia Inhibitory Factor (Lif)mentioning
confidence: 80%
“…Interestingly, a recent study revealed that myelin-specific T cell lines express LIF in vitro [58]. Since T cells and macrophages may also produce LIF in MS lesions in situ, infiltrating immune cells may also exert a protective effect on oligodendrocytes.…”
Section: Leukaemia Inhibitory Factor (Lif)mentioning
confidence: 99%
“…This is in contrast to LIF-overexpressing mice which are characterized by interconversion of thymic and lymph node morphologies (13). LIFR␤ is present in Ag-activated T cell blasts and LIF is produced by monocytes, macrophages, and also T cells (30,31), thus opening the possibility of paracrine actions. Yet, similar to previous studies (9,32), exogenous addition of LIF to MOG-primed T cell cultures does not have any additional effect on T cell proliferation and adoptive transfer of WT T cells in LIF Ϫ/Ϫ mice does not change the course of EAE.…”
Section: Discussionmentioning
confidence: 91%
“…In addition to these experiments, we also performed studies to compare the effects of IL-11 to those of LIF, another cytokine of the gp130 family that has previously been implicated in oligodendrocyte protection and myelin formation in rodent systems (Mayer et al, 1994;Gard et al, 1995;Butzkueven et al, 2002;Ishibashi et al, 2005;Vanderlocht et al, 2006). Primary human fetal oligodendrocyte-enriched cultures were treated at plating with 10 ng/ml recombinant IL-11 or LIF, and allowed to grow and mature as above before being fixed, stained, and analyzed.…”
Section: Il-11 Potentiates the Survival And Maturation Of Primary Hummentioning
confidence: 99%